2022
DOI: 10.1055/a-1916-0229
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cervical Joint Position Sense in Computer Users with Neck Pain, Forward Head Posture, Asymptomatic and Non-Computer Users – A Cross-Sectional Study

Abstract: Purpose People use computers in offices and workplaces daily to perform different activities. Impaired cervical proprioception and forward head posture (FHP) may contribute to the development and maintenance of neck pain in computer users. The aims of this study are 1) to compare cervical joint position sense (JPS) in computer users with neck pain, with FHP, healthy computer users, and healthy non-computer users… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 52 publications
0
5
1
Order By: Relevance
“…Therefore, computer users with neck pain had a significant positive correlation with cervical JPE. 26 However, the current research did not find a significant association between time spent using a gadget and CP. This finding was inconsistent with the previous study, which found that prolonged use of a tablet computer in a head-forward, neck-flexed posture did not significantly increase cervical JPE.…”
Section: Discussioncontrasting
confidence: 85%
“…Therefore, computer users with neck pain had a significant positive correlation with cervical JPE. 26 However, the current research did not find a significant association between time spent using a gadget and CP. This finding was inconsistent with the previous study, which found that prolonged use of a tablet computer in a head-forward, neck-flexed posture did not significantly increase cervical JPE.…”
Section: Discussioncontrasting
confidence: 85%
“…In addition, it influences re-education and motor learning. [9,10]. Impaired position sense reduces the capacity to maintain joint stability and impairs postural control and bodily balance [11].…”
Section: Introductionmentioning
confidence: 99%
“…Cervical joint position sense (JPS) in the neck region can be evaluated using various techniques, such as the target head-positioning tests, ultrasound-based kinaesthetic evaluation systems, and three-dimensional FASTRAK measurement procedures [12]. Although it is not the gold standard, the target head-repositioning test employing a cervical range of motion (CROM) device is the most employed method in scientific research [9,[13][14][15]. The multitude of receptors in the cervical joint, capsule, ligament, and peri-articular structures transmits afferent proprioceptive signals to the higher centers and contributes to efficient proprioception [16].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous researchers have investigated the association between the aging process and structural changes in the articular and cutaneous receptors [ 21 , 37 , 38 ]. In addition, age-related changes in the central nervous system, including the brain and spinal cord, can also contribute to impaired proprioception [ 26 , 32 , 33 , 34 , 35 , 37 , 39 , 40 , 41 , 42 , 43 , 44 ]. This can result in the slower processing of proprioceptive information, leading to a reduced ability to accurately perceive joint position and movement [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reduced proprioception was nearly four times more detrimental to the subjects’ ability to maintain their balance than decreased visual input [ 45 ]. Yet, when both proprioception and visual input were reduced, the relative chance of losing balance increased by 5.7 to 7.4 times [ 43 ]. Not only does diminished muscular strength affect older adults’ balance, but so does diminished sensory input: the adjusted odds of losing balance dropped by 20% for every Nm/kg increase in the subject’s muscle strength [ 16 ].…”
Section: Discussionmentioning
confidence: 99%